Pen-type laser fluorescence device versus bitewing radiographs for caries detection on approximal surfaces. Issue 1 (December 2016) - Bizhang, M.; Wollenweber, N.; Singh-Hüsgen, P.; Danesh, G.; Zimmer, S.
Abstract Background The accurate detection of approximal caries is generally difficult. The aim of this study was to assess the ability of the pen-type laser fluorescence device (LF pen) to detect approximal carious lesions in comparison to bitewing radiographs (BW). Methods Three hundred forty-one tooth surfaces were diagnosed in 20 patients with an average age of 26.70 (±2.82) years. Each test tooth was sequentially assessed by a single calibrated examiner using visual inspection, BW, and the LF pen. Radiographs were used as the gold standard to calculate an appropriate cut-off. Results Sensitivity, specificity and accuracy values for cut-off limits of 15, measured by the LF pen were compared using the chi2 test (McNemar test). For approximal caries at D3 level, the highest values of specificity and sensitivity were observed for the LF pen at a cut-off value of 15 (96.8 and 83.0 %) and for visual inspection (99.3 and 4.3 %). Conclusion Within the limitations of this study, dentin caries on approximal surfaces could be detected equally well by the LF pen as by the bitewing radiographs. Therefore, the LF pen can be recommended as an alternative to radiographs for the detection of approximal caries in a regular dental practice setting. Trial registration DRKS00004817 on DRKS on 12th March 2013.